2020
DOI: 10.3389/fmed.2020.00221
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Hyperparathyroidism, Secondary to a Reduction in Kidney Function, in Individuals With Vitamin D Deficiency

Abstract: Aims/Introduction: Chronic kidney disease (CKD)-mineral and bone disorders (CKD-MBD) are an adverse outcome derived from decreases in kidney function, where abnormality of serum concentrations of calcium (Ca), phosphorus, parathyroid hormone (PTH), and vitamin D can be seen simultaneously. To identify individuals at risk for CKD-MBD or secondary hyperparathyroidism, the relationships between estimated glomerular filtration rate (eGFR) and serum PTH concentration were evaluated, allowing for confounding factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…According to a systematic review and meta-analysis of twenty-two studies related to vitamin D supplementation in CKD, there was a significant decline in PTH levels with vitamin D supplementation [20]. Additionally, the analysis of eGFR and serum PTH concentration in nine hundred and thirty people from the general Japanese population revealed that eGFR < 60 ml/min/1.73m 2 is a significant risk factor for an increase in PTH levels, albeit the relationship was present only in participants with vitamin D deficiency [21].…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review and meta-analysis of twenty-two studies related to vitamin D supplementation in CKD, there was a significant decline in PTH levels with vitamin D supplementation [20]. Additionally, the analysis of eGFR and serum PTH concentration in nine hundred and thirty people from the general Japanese population revealed that eGFR < 60 ml/min/1.73m 2 is a significant risk factor for an increase in PTH levels, albeit the relationship was present only in participants with vitamin D deficiency [21].…”
Section: Discussionmentioning
confidence: 99%
“…This study involved patients with stage 3 to 5 CKD. A Japanese study showed that a reduction in the eGFR to < 60 mL/min/1.73 m 2 with deficient vitamin D is a significant risk factor for an increased serum PTH concentration 22 . To highlight a more typical effect, we selected more representative sample data.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Kidney Disease (CKD) is a world health problem [1]. Global estimates of CKD indicate its prevalence in 14,3% of the general population and 36,1% of risk groups.…”
Section: Introductionmentioning
confidence: 99%